NAFTA, Social Unionism, and Labour Movement Power in Canada and the United States - Robinson, Ian (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1994)
This paper considers how the North American Free Trade Agreement (NAFTA) is likely to affect labour movement power in Canada and the United States. The paper is divided into four parts. It first defines the concept of « labour movement power », breaking it down into its component parts. It next considers why we should care about what happens to labour movement power. It then outlines the principal negative and positive effects that the NAFTA is likely to have on labour movement power. Attention is also given to the beneficial consequences that the fight against the NAFTA has already had for the labour movement. It is argued that the NAFTA 's negative impacts are likely to outweight its positive ones in the short run and that the positive effects could substantially outweight its negative effects over the medium to long run. Whether it does will depend upon choices made in the next few years by labour movement leaders and activists.